2021
DOI: 10.1093/plphys/kiab053
|View full text |Cite
|
Sign up to set email alerts
|

TCP transcription factors suppress cotyledon trichomes by impeding a cell differentiation-regulating complex

Abstract: Trichomes are specialized epidermal cells that act as barriers against biotic and abiotic stresses. Although the formation of trichomes on hairy organs is well studied, the molecular mechanisms of trichome inhibition on smooth organs are still largely unknown. Here, we demonstrate that the CINCINNATA (CIN)-like TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) transcription factors inhibit the formation of trichomes on cotyledons in Arabidopsis (Arabidopsis thaliana). The tcp2/3/4/5/10/13/17 septuple mutant produces coty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…Leaf shape is a complex trait controlled by multiple genes and is of great significance for plant photosynthetic energy storage and resistance to stress ( Testone et al, 2019 ; He P. et al, 2020 ). Teosinte branched1, cycloidea, and proliferating cell factors (TCPs), belonging to the bHLH transcription factor family, are widely involved in leaf morphology regulation ( Aggarwal et al, 2010 ; Zhao M. L. et al, 2020 ; Lan et al, 2021 ). Previous studies have confirmed that TCP transcription factors widely participate in the regulation of flower shape, leaf shape, and stem and root development and have been identified in many plant species ( Wang et al, 2019 ; He J. et al, 2020 ; Wen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf shape is a complex trait controlled by multiple genes and is of great significance for plant photosynthetic energy storage and resistance to stress ( Testone et al, 2019 ; He P. et al, 2020 ). Teosinte branched1, cycloidea, and proliferating cell factors (TCPs), belonging to the bHLH transcription factor family, are widely involved in leaf morphology regulation ( Aggarwal et al, 2010 ; Zhao M. L. et al, 2020 ; Lan et al, 2021 ). Previous studies have confirmed that TCP transcription factors widely participate in the regulation of flower shape, leaf shape, and stem and root development and have been identified in many plant species ( Wang et al, 2019 ; He J. et al, 2020 ; Wen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors, such as homo-dimers and hetero-dimers, often build combinations or interact with other proteins rather than acting alone to perform their complex biological functions [ 8 ]. Moreover, studies have shown that TCP s belonging to the CIN group can inhibit MYB gene-related transcripts and protein complexes at the transcription and protein levels [ 21 ], indicating that TCP members can form a regulatory network through interactions with other genes. The TCP s module, consisting of Class I and Class II TCP proteins, has been reported to manipulate important development processes, including hormone homeostasis in Arabidopsis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCP transcription factors inhibit the formation of trichomes on the side of Arabidopsis ( Arabidopsis thaliana (L.) Heynh.) cotyledon, thus affecting the barrier function of these trichomes against biotic and abiotic stresses on the plant [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that trichome formation in Arabidopsis is regulated by a few key regulators including TTG1, GL1, GL3/EGL3, GL2 and the R3 MYB transcription factor [3][4][5][6][7]. Some other regulators such as GIS proteins GIS and GIS3, ZINC FINGER proteins ZFP5 and ZFP8, SPL protein SPL9, and NAC protein NTL8, and several TCP proteins are also involved in the regulation of trichome formation either via regulating the expression of the MBW complex component genes [25][26][27][28][29][30][31][32], or affecting the formation or activation of the MBW complex [33]. We show that SVB and SVB2 function redundantly to regulate trichome formation in Arabidopsis (Figures 6 and 9), and we found that the expression of EGL3 is affected in the svb svb2 double mutants (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the C2H2 transcription factors GLABROUS INFLORESCENCE STEMS (GIS) and GIS3, and the ZINC FINGER transcription factors ZINC FINGER PROTEIN 5 (ZFP5) and ZFP8 regulate the expression of the MBW complex component genes [25][26][27][28][29], the plant-specific transcription factor SQUAMOSA PROMOTER BINDING PROTEIN LIKE (SPL) transcription factor SPL9 and the NAM, ATAF1/2, and CUC (NAC) transcription factor NTM1-LIKE 8 (NTL8) directly regulates the expression of R3 MYB genes TRY and TCL1 [30,31], whereas the CINCINNATA-like TEOSINTE BRANCHED1-CYCLOIDEA-PCF (TCP) transcription factor TCP4 directly regulate the expression of R3 MYB genes TCL1 and TCL2 [32]. On the other hand, the TCP proteins such as TCP2, TCP3, TCP4, TCP5, TCP10, TCP13, TCP17 and TCP24 can interact directly with GL3, therefore affecting the formation of the MBW complex [33].…”
Section: Introductionmentioning
confidence: 99%